Impulse Buying Behavior of Retail Consumers - Wiyono Wiyono; Haryanto Haryanto; Dwi Hastjarja K. B. (Faculty of Economics and Business, Jenderal Soedirman University, 2017)
Retail competition in Indonesia is increasingly competitive after an international retail policy can take place in Indonesia directly. The real impact, international retail dominance over national (local) retail is increasingly seen, especially seen based on sales turnover. The competition requires the right strategy. This study aims to explore retail consumer behavior in Surakarta. The result of exploration shows that the main factor of decision of retail selection is retail location (28%). Further factor of price (21%) and merchandise (15%). In addition, consumer shopping behavior shows that consumers when in shopping is not alone. Subsequent findings indicate that most consumers do not make written planning when shopping so often buy products that are outside the initial planning (impulse buying). This is further strengthened when there is promotion (41%) and product placement strategy (23%). While the results of SEM-PLS analysis, the relationship between the variables that are constructed indicated that the variable of merchandise and in-store promotion has an effect on impulse buying. Product quality and price variable do not affect impulse buying. Furthermore, money available variable is not a moderating variable between in-store promotion and impulse buying.